'It's not a linear thing; there are a lot of intersecting circles': Factors influencing teachers' implementation of Meaningful Physical Education. (September 2022) - Beni, Stephanie; Fletcher, Tim; Ní Chróinín, Déirdre
Abstract: The purpose of this research was to examine factors that influenced how 12 elementary teachers implemented the Meaningful Physical Education innovation in their classrooms. Qualitative data were collected over 15 months. Analysis was guided conceptually by factors that influence innovation implementation. Results showed that implementation was most strongly influenced by teachers' prior experiences and beliefs, teachers' perceptions of students' responses to the implementation process, and external organizational pressures. The longitudinal nature of this research offers an important contribution to the literature on implementation of education innovations.